2001
DOI: 10.1007/bf02704018
|View full text |Cite
|
Sign up to set email alerts
|

Surface studies on as-grown (111) faces of sodium bromate crystals

Abstract: Single crystals of sodium bromate are grown at various supersaturations ranging from 3% to 8%. Surface studies have been carried out on as-grown and etched (111) faces of these crystals. Typical and systematically oriented growth hillocks are observed almost on all the faces. Further dislocation studies are made to understand the growth history of these crystals. These studies suggest that the crystals grow by 2D-growth mechanism. In addition to this, studies are also conducted on the formation of overgrowths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 9 publications
2
12
0
Order By: Relevance
“…In conventional solution technique, many of the commonly observed characteristic growth induced defect structures comprising growth sector boundaries [3], liquid inclusions [3,4], growth band [5], slip band [6], low angle grain boundaries [7], dislocations [8], vacancies [8], cracks, stacking faults [9] and twins can be attributed to impurities. Growth bands are layers of varying impurity content and it is usually observed in solution grown crystals caused by fluctuations in the growth conditions [10] as well as growth sector boundaries [11].…”
Section: Introductionmentioning
confidence: 99%
“…In conventional solution technique, many of the commonly observed characteristic growth induced defect structures comprising growth sector boundaries [3], liquid inclusions [3,4], growth band [5], slip band [6], low angle grain boundaries [7], dislocations [8], vacancies [8], cracks, stacking faults [9] and twins can be attributed to impurities. Growth bands are layers of varying impurity content and it is usually observed in solution grown crystals caused by fluctuations in the growth conditions [10] as well as growth sector boundaries [11].…”
Section: Introductionmentioning
confidence: 99%
“…Liquid inclusions getting trapped parallel to the interfaces are due to drastic changes in growth condition [13]. In general, it is observed that almost all the conventional method-grown crystals (ADP, KDP, NaBr, BaNO 3 , KAl (SO 4 ) 2 , LAHF) contain inclusions [13][14][15][16]. In SR method as there are no such growth fluctuations or non-uniform growth rates the dislocations of the above causes are avoided.…”
Section: Chemical Etching Analysismentioning
confidence: 89%
“…A number of parameters such as variation in supersaturation during the growth, non-uniform growth rates, etc., are responsible for the formation of inclusions. Liquid inclusions getting trapped parallel to the interfaces are due to drastic changes in growth condition [13]. In general, it is observed that almost all the conventional method-grown crystals (ADP, KDP, NaBr, BaNO 3 , KAl (SO 4 ) 2 , LAHF) contain inclusions [13][14][15][16].…”
Section: Chemical Etching Analysismentioning
confidence: 97%
“…EPD for conventional and SR grown TGBC is 3.9 Â 10 2 and 1.4 Â 10 2 cm À2 , respectively. In general, it is observed that almost all the conventional method grown crystals (ADP, KDP, NaBr, BaNO 3 , KAl (SO 4 ) 2 ) contain inclusions [5][6][7][8]. Larger inclusions usually emit bundles of many dislocations [5].…”
Section: Etching Analysismentioning
confidence: 97%
“…A variety of parameters such as variation in supersaturation during the growth, non-uniform growth rates, etc., are responsible for the formation of inclusions. Liquid inclusions getting trapped parallel to the interfaces are due to drastic changes in growth condition [7]. It is a common observation that inclusions generate growth dislocations.…”
Section: Article In Pressmentioning
confidence: 99%